The effect of abiotic factors on apricot yield in the Southern Urals - F. M. Gasymov (Труды по прикладной ботанике, генетике и селекции, 2019)
The productivity of apricot plantations in the Urals is limited by the irregularity of fruiting due to poor fruit bud winter hardiness in a majority of introduced cultivars. In 1999–2016, a research project was underway at the Department of Horticulture, Southern Ural Research Institute of Horticulture and Potato Growing, aimed at studying the apricot collection accessions of diverse geographic origin under the climate conditions of the Southern Urals. Such a long-term study made it possible to identify abiotic factors affecting the yield of this crop as well as to select highly adaptive and high-yielding cultivars for the Southern Urals: ‘Prizer’ (9.4 kg/tree), ‘Snezhinsky’ (9.2 kg/tree), ‘Kichiginsky’ (9.0 kg/tree) and ‘Uralets’ (8.5 kg/tree). Among the studied genotypes there were tree forms with irregular fruiting pattern, characterized by low resistance to adverse effects of abiotic factors: ‘Khabarovsky’ (0.9 kg/tree) and ‘Michurinsky No. 22’ (0.3 kg/tree). In the environments of the Southern Urals, critical winters (continuous frosts of –40°C) considerably damage generative buds, which results in having no apricot harvest in such years. Despite the harsh winters, annual shoots of local apricot-trees tended to freeze only to a small degree. Field survey of the apricot plantations showed that generative buds of local apricot cultivars (‘Kichiginsky’, ‘Prizer’, ‘Snezhinsky’ and ‘Uralets’) could withstand frosts of –40... –43°С (2003) only if they were brief, while continuous frosts destroyed them completely (2006, 2010). In addition, a decline in harvest was observed as a result of springtime frosts and temperature fluctuations in the end of winter (1999, 2014). Despite the abundant flowering in 2001, 2015 and 2016, the yield of apricot trees was low due to the frosts during the flowering period. Productivity of apricot trees also depends on their genetic characteristics, and in particular, on the geographical origin of cultivars. The introduced cultivars ‘Khabarovsky’ and ‘Michurinsky No. 22’ yielded fruit only thrice during the entire period of research.